Dependence of Immunoglobulin Class Switch Recombination in B Cells on Vesicular Release of ATP and CD73 Ectonucleotidase Activity - Francesca Schena; Stefano Volpi; Caterina Elisa Faliti; Federica Penco; Spartaco Santi; Michele Proietti; Ursula Schenk; Gianluca Damonte; Annalisa Salis; Marta Bellotti; Franco Fais; Claudya Tenca; et al. (Cell Reports, 2013)
Immunoglobulin (Ig) isotype diversification by class switch recombination (CSR) is an essential process for mounting a protective humoral immune response. Ig CSR deficiencies in humans can result from an intrinsic B cell defect; however, most of these deficiencies are still molecularly undefined and diagnosed as common variable immunodeficiency (CVID). Here, we show that extracellular adenosine critically contributes to CSR in human naive and IgM memory B cells. In these cells, coordinate stimulation of B cell receptor and toll-like receptors results in the release of ATP stored in Ca2+-sensitive secretory vesicles. Plasma membrane ectonucleoside triphosphate diphosphohydrolase 1 CD39 and ecto-5′-nucleotidase CD73 hydrolyze ATP to adenosine, which induces CSR in B cells in an autonomous fashion. Notably, CVID patients with impaired class-switched antibody responses are selectively deficient in CD73 expression in B cells, suggesting that CD73-dependent adenosine generation contributes to the pathogenesis of this disease.